Enhancement in the Dielectric Property of Thick Lead Zirconium Titanate Films under UV Illumination. Issue 15 (31st May 2021) - Vandana,; Gupta, Reema; Tomar, Monika; Tandon, Ram Pal; Gupta, Vinay
Abstract : This work studies the effect on dielectric properties of lead zirconium titanate (Pb1.1 Zr0.4 Ti0.6 O3 [PZT]) thick films under UV light illumination (wavelength =325 nm) for the realization of tunable capacitors. A modified sol–gel technique is utilized for the growth of polycrystalline PZT thick films on nickel substrate. The PZT films are deposited on Ni, and three different temperatures (450, 550, and 650 °C) are selected for annealing the samples in air atmosphere. Dielectric studies are performed on the optimized films, under varying intensities of UV radiation. Enhanced dielectric constant values are observed under UV illumination for the PZT films annealed at 550 and 650 °C due to generation of photocarriers and induced oxygen vacancies. An appreciable change in dielectric constant of about 75% at 1 MHz frequency is seen for the PZT film fabricated at higher annealing temperature (650 ºC) under UV illumination (intensity = 12 mW cm −2 ). The obtained results are encouraging for the utilization of thick PZT films in tunable capacitors. Abstract : Variation of dielectric constant of a Pb1.1 Zr0.4 Ti0.6 O3 (PZT) thick film with frequency (in the presence and the absence of UV radiation) at an annealing temperature of 650 °C (inset: dielectric measurement setup under UV illumination).